Angiogenic factors and the risk of preeclampsia: A systematic review and meta-analysis - Yousef Veisani; Ensiyeh Jenabi; Ali Delpisheh; Salman Khazaei (Shahid Sadoughi University of Medical Sciences, 2019)
Background The etiological nature of preeclampsia is heterogeneous. The use of biomarkers indices in early pregnancy helps to have appropriate stratification of pregnancies into high- and low risk for the purpose of choosing timely interventions. Objective The aim of this systematic review was to determine the pathogenic role of soluble soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) in the prediction of preeclampsia in women. Materials and Methods We performed a systematic search of the international databases including PubMed, Scopus, and Web of Science until August 2017. The quality of included studies was assessed using the Newcastle-Ottawa Scale. The primary outcome in this review was preeclampsia. The statistical heterogeneity was assessed using the X 2 test and quantified by I 2 . Pooled effects size was obtained by random effects model. Subgroup analyses were also carried out. Results Totally, 284 records were identified in the initial search and 15 records were finally included in the meta-analysis. The pooled odds ratios (ORs) for the association between the high level of sFlt-1 and low level of PlGF and subsequent development of preeclampsia among women were 5.20 (95% CI: 1.24-9.16) and 2.53 (95% CI: 1.33-3.75), respectively. The mean difference for sFlt-1 and PlGF in women with preeclampsia compared to controls was 1.15 (95% CI: 0.43-1.86) and -0.94 (95% CI: -1.37-0.52), respectively. Conclusion According to the results from this meta-analysis, increased levels of sFlt-1 and reduced levels of PlGF predict the subsequent development of preeclampsia.